Tyrosinase Enzyme Inhibition Activity Test by Ethanol Extract of Taro Leaf (Typhonium flagelliforme (Lodd.) Blume) In Vitro - Sholikha, Munawarohthus; Wahyuningtyas, Wahyuningtyas; Puspitasari, Lia (Sainstech Farma: Jurnal Ilmu Kefarmasian, 2023)
Hyperpigmentation is an event that occurs due to excessive production of skin pigment. Skin color is strongly influenced by the presence of melanin, where the presence of melanin is strongly influenced by the enzyme tyrosinase. Taro leaf (Typhonium flagelliforme (Lodd.) Blume) are one of the plants have flavonoid compounds used as antioxidants and tyrosinase inhibitors. The aim of this study was to test the ethanol extract of taro leaf as a tyrosinase inhibitor. Taro leaf in this study were obtained through an extraction process using 96% ethanol solvent by maceration method. The thick ethanol extract of taro leaf was tested for phytochemical screening, total flavonoid levels, and tyrosinase inhibition test. The method used for tyrosinase inhibition test was enzymatic method in vitro. The results of this study indicated that there was a total flavonoid compound content of 0.7378% (b/b) and the inhibitor activity can be seen from the IC50 value for the diphenolation reaction (L-DOPA substrate) which was 13.307 mg/mL. This value was greater when compared with 0.093 mg/mL of phenolic acid, so that the ethanol extract of taro leaf has the potential to inhibit tyrosinase activity.